The Balakrishnan-Alpha-Beta-Skew-Laplace Distribution: Properties and Applications - Sricharan Shah; Partha Jyoti Hazarika; Subrata Chakraborty; Morad Alizadeh (Statistics, Optimization & Information Computing, 2022)
In this paper, a new form of alpha-beta-skew-Laplace distribution is proposed under Balakrishnan [3] mechanism and investigated some of its related distributions. The moments, distributional properties and some extensions of the proposed distribution have also studied. Finally, the suitability and the appropriateness of the proposed distribution has tested by conducting data fitting experiment and comparing the values of Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC) with the values of some other related distributions. Likelihood Ratio test is used for discriminating between the nested models.